A COMPARATIVE STUDY OF EFFICACY OF DIFFERENT TYPES OF TWO-HANDED MASK VENTILATION TECHNIQUES IN ANAESTHETISED APNOEIC ADULTS - Dr. Vyshnavi S; Dr. Ashwini N; Dr. Akkamahadevi P; Dr. Darshini S; Dr. Vivek S (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
ABSTRACT BACKGROUND: Bag mask ventilation is an important and basic airway management skill. Providing adequate bag mask ventilation in an effective manner can reverse the effect of hypoxia thereby rescuing the patient from potential brain damage as well as death if intubation is impossible. Two handed C-E technique and V-E technique mask ventilation are commonly used for maintaining mask ventilation in apneic patients. In this study we wanted to compare the efficacy of the C-E and V-E techniques of mask ventilation in terms of expired tidal volume. METHODS: 80 patients of ASA PS I/II posted for general surgeries under general endotracheal anaesthesia were taken for the face mask ventilation study after obtaining written informed consent from them at JSS Medical College and Hospital, Mysuru. Patients were allocated into the C-E and V-E techniques by random computer allocation. They were then preoxygenated with an anatomical face mask with 100% oxygen, and anaesthesia was induced using standard institutional protocol. RESULTS: There is a significantly higher tidal volume generated for the V-E technique compared to the C-E technique irrespective of the order of ventilation (P value of 0.001), with a mean of 490.82 mL for the C-E and 515.41 mL for the V-E. On comparing average tidal volumes in C-E to V-E order, we found a significantly higher value for V-E than C-E (p-value 0.002). On comparing average tidal volumes in V-E to C-E order, we found a significantly higher value for V-E than C-E (p-value of 0.001). In V-E, we found higher peak inspiratory pressure irrespective of the presentation (p-value of 0.0001). CONCLUSION: Of the different techniques of two-handed mask ventilation employed, significantly higher tidal volume is generated with the V-E technique in comparison with the C-E technique, and it is concluded that the V-E technique is superior to the C-E technique.